EFFECT E-SERVICE QUALITY ON CUSTOMER SATISFACTION AND IMPACT ON REPURCHASEIN LAZADA INDONESIA’S ONLINE SELLING IN THE CITY OF SEMARANG - Amelia Saraswati; Farida Indriani (International Journal of Economics, Business and Accounting Research (IJEBAR), 2021)
This research was conducted by researching the gap between the relationship between e-service quality and customer satisfaction and its effect on repurchase interest. The study was conducted to see whether all variables of electronic service quality (usage, website design, responsiveness, personalization / customization, and assurance) had an effect on the total service quality and customer satisfaction which could lead to repurchase. The analysis technique used is SEM (structural equation modeling) with the number of respondents as many as 197 Lazada customers in the city of Semarang. The results of the criteria for goodness of fit RMSEA = 0.066; NFI & NNFI = 0.96 & 0.94; IFI = 0.92; and RFI = 0.93. These results indicate that the model has a good fit and is feasible to use. Based on the research results, there are four hypotheses that have a positive and significant effect, namely, web design, responsiveness, customization, and customer satisfaction on repeat purchase intention. However, there were two objections that were rejected, namely the use of (ease of use) and assurance (assurance) of repeat purchase intentions. Keywords : e-service quality, customer satisfaction, repurchase intentions, Lazada.